PENGARUH TINGKAT KEMASAKAN BENIH DAN METODE KONSERV ASI TERHADAP VIGOR BENIH DAN VIGOR KACANG JOGO (Phaseolus vulgaris L.) - Elis Kartika; Satriyas IIyas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1994)
The purpose of this experiment was to investigate the effect of various levels of seed maturity and conservation methods on seed vigor and seedling vigor of broad bean( Phaseolus vulgaris L.). The experiment was conducted at Darmaga IV Experimental Station, seed Science and Technology Laboratory - Leuwikopo IPB and BIOTROP, Tajur. Broad bean no. 1058 was used in this experiment. Seed vigor testing was carried out in the laboratory, using Completely Randomized Design, while Randomized Complete Block Design was applied to field experiment for testing seedling vigor. The treatment consisted of two factors as followed:(I) Levels of seed maturity: MI = 27 daf (days after flowering), M2 = 30 daf, M3 = 33 daf, M4 = 36 daf, and M5 = 39 daf (2) Conservation methods: K 1 = pods were spread out in the processing unit room for about 1 week, the seed moisture content was dropped to 40%; K2 = sun drying; K3 = artificial drying, using seed dryer 400C. Seed moisture content was dropped to 9 - 10% in K2 and K3 methods. Broad bean seeds harvested at 36 daf, the time when physiological maturity was reached, followed by either sun drying or artificial drying, showed a maximum seed vigor. However, a higher seedling vigor resulted from sun drying as compared to artificial drying. Before physiological maturity seed vigor and seedling vigor was still lower, while the vigor was reduced after physiological maturity.